2011
DOI: 10.1002/pros.21473
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of putative cancer stem cell markers in primary prostate cancer is associated with progression of bone metastases

Abstract: It can be concluded that percentage of stem cell-like prostate cancer cells has a prognostic impact especially on the risk of metastatic bone progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Enhanced integrin α 2 expression was shown to facilitate the adhesion and survival of PCa cells through activated FAK and Akt phosphorylation (Figure 2). High expression of integrin α 2 in metastatic PCa and its important role in cell survival and adhesion in the bone microenvironment is supported by recent experimental and clinical publications [53, 54]. 3) Concomitant with enhanced integrin α 2 expression, we also observed that LNCaP RANKL cells grown in 3-D suspension exhibited elevated functional AR expression, a result not seen in 2-D monolayer culture (Figure 3).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Enhanced integrin α 2 expression was shown to facilitate the adhesion and survival of PCa cells through activated FAK and Akt phosphorylation (Figure 2). High expression of integrin α 2 in metastatic PCa and its important role in cell survival and adhesion in the bone microenvironment is supported by recent experimental and clinical publications [53, 54]. 3) Concomitant with enhanced integrin α 2 expression, we also observed that LNCaP RANKL cells grown in 3-D suspension exhibited elevated functional AR expression, a result not seen in 2-D monolayer culture (Figure 3).…”
Section: Discussionsupporting
confidence: 80%
“…These results are in agreement with work of Colombel et al . [54] who showed that higher α 2 β 1 protein expression in primary PCa tissues correlates with bone metastasis. Additionally, Sottnik et al .…”
Section: Discussionmentioning
confidence: 99%
“…37). In addition, the signatures of PCSCs are associated with prostate cancer bone metastasis and poor prognosis (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of CSCs had a prognostic impact, particularly on the risk of progression of bone metastases. 32 The percentage of cells expressing a stem cell phenotype in bone marrow metastases of prostate cancer patients has been shown to be predictive of bone metastases progression. 33 There is also a small population of docetaxel-resistant cells, likely CSCs, that have been shown to be higher in metastasic compared to primary patient samples, and, in primary untreated samples, the percentage of these cells was associated with prognostic factors and time to biochemical relapse.…”
Section: Role Of Cscs In Prostate Cancermentioning
confidence: 99%